Participation as a Framework for Analysing Consumers' Experiences of Alternative Dispute Resolution (ADR). (15th May 2020) - Williams, Jane; Gill, Chris; Creutzfeldt, Naomi; Vivian, Nial
Abstract: This article argues that an analytic framework based on participation is useful for analysing consumer experiences of alternative dispute resolution (ADR), providing a complementary approach to analyses drawing on procedural justice theory. The argument is developed by applying McKeever's 'ladder of legal participation' (LLP) 1 to a qualitative data set consisting of interviews with United Kingdom consumers. The article concludes that applying the LLP in the consumer ADR context results in novel empirical and theoretical insights. Empirically, it demonstrates that – even in low‐value and transactional disputes – consumers expect high levels of participation from ADR. Theoretically, it argues that the LLP complements existing approaches by providing an unifying lens through which to study consumer experiences by emphasizing the importance of participation, not only as a process value but also in shaping outcomes highlighting the distinction between genuine and tokenistic provision of ADR.